2005
DOI: 10.1177/154405910508401105
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Activation in Human Dental Pulp Stem Cells by TNF and LPS

Abstract: Post-natal human dental pulp stem cells (DPSCs) represent a unique precursor population in the dental pulp, which has multipotential and can regenerate a dentin/pulp-like structure. Because the dental pulp is frequently infected by oral bacteria due to dental decay, in this study, we examined whether lipopolysaccharide (LPS) and tumor necrosis factor (TNF) activated the immunologic transcription factor nuclear factor kappa B (NF-kappaB) in DPSCs. We found that both TNF and LPS activated the I-kappa B kinase co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
130
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(141 citation statements)
references
References 29 publications
5
130
0
1
Order By: Relevance
“…NF-B consists of homo-and heterodimeric complexes of the Rel family proteins, including p50, p52, p65/RelA, c-Rel, and RelB. In mammalian cells, the most widely distributed B-binding activity is a heterodimer of p50 and p65/RelA proteins, in which the p65/RelA subunit has potent transactivation activity (17)(18)(19). The IKK complex is critical for NF-B activation induced by LPS and proinflammatory cytokines.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…NF-B consists of homo-and heterodimeric complexes of the Rel family proteins, including p50, p52, p65/RelA, c-Rel, and RelB. In mammalian cells, the most widely distributed B-binding activity is a heterodimer of p50 and p65/RelA proteins, in which the p65/RelA subunit has potent transactivation activity (17)(18)(19). The IKK complex is critical for NF-B activation induced by LPS and proinflammatory cytokines.…”
mentioning
confidence: 99%
“…The IKK complex is critical for NF-B activation induced by LPS and proinflammatory cytokines. The IKK complex is mainly composed of two catalytic subunits, IKK␣ and IKK␤, and IKK␥ (also known as NF-B essential modulator), a scaffold molecule without catalytic activity (17)(18)(19)(20).…”
mentioning
confidence: 99%
“…LPS in infected pulp tissues of pulp canal could activate LYMs and FBs producing pro-inflammatory cytokines such as TNF and IL-1 (Chang et al, 2005). Some studies have suggested that FBs could be activated to secret inflammatory cytokines, such as NLRP3 and IL-33, after stimulation of inflammation and participate in infiltration, cell transport, and tissues fibrosis in the tissue repair process (Liu and Liu, 2013;Sipert et al, 2014;Velickovic et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…TLR activation results in proinflammatory cytokine secretions such as interleukin-1, tumor necrosis factor-alpha, interleukin-8, interleukin-10, and interferons (27,28). Different types of TLRs recognize different antigenic substances, and the specific location of TLR specify the form of the ensuing immuno-inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%
“…The mucosal reaction to pathogenic bacteria or permeated antigens also activates the postreceptor NF-κB pathway which is the main pathway of adaptive immunity (13,27). A growing number of studies demonstrate that aberrant NF-κB signaling is critical in the development of various inflammatory diseases (13,14,28,29). NF-κB pathway may be activated by Toll-like receptors/pathogen signals, and proinflammatory cytokins (29).…”
Section: Discussionmentioning
confidence: 99%